“La relación escuela-familia en el aprendizaje intercultural” - Caiza Parra, Janeth Alejandra (2022)
Today education is the reflection of teamwork between the family and the school, since both have shared responsibilities for the correct pedagogical process of the student. When parents are involved in their children's education, they achieve better results, have positive attitudes toward school, and grow to be successful in life. This research project addressed the problem of how the school-family relationship influences the intercultural learning of seventh year EGB students. The objective was to strengthen the school-family relationship, through a training workshop, for the improvement of intercultural learning. The methodology used was based on the interpretive paradigm, since it allowed us to understand the reality of the educational and social context of the research subject. Also, qualitative research was used giving relevance to the elaboration of the theoretical framework and the proposal of this project; In this way, bibliographic research was also used when using books, encyclopedias, articles written by other authors, in the same way field research because they went to the place of events to observe the problem, on the other hand, the inductive and statistical method was applied. , given that this method processes and analyzes the data obtained to later execute the analysis and interpretation of the information, since, with the tabulation, the data obtained was interpreted, through the statistical method; using the Excel program. Techniques such as the survey with its proper instrument were selected: the questionnaire applied to students, parents, teachers and authority of the educational institution, then the process was carried out to establish the conclusions and recommendations of the project, emphasizing that parents family are not committed to the education of their children, as well as, they are not concerned about their achievements, advances of their representatives as well as the different activities that take place in the institution, which directly affects their training. Therefore, it is recommended that parents attend the training workshop to raise awareness of the importance of interacting with their child inside and outside the classroom.